Postoperative Pain Control Using Regional Nerve Blocks in Breast Cancer Surgery Mastectomy - Rimsha Abid; Ruqaya Khurshid; Muhammad Awais; Fahad Kaleem; Kamran Shabir; Muhammad Arslan; Ammar Farooq; Ajmal Shahbaz (Journal of Health, Wellness and Community Research, 2025)
Background: Postoperative pain management remains a critical challenge in breast cancer surgery, with conventional opioid-based analgesia associated with significant side effects and suboptimal patient outcomes. The role of regional nerve blocks in optimizing pain control and minimizing opioid use has not been comprehensively assessed in local patient populations, highlighting a relevant gap in clinical practice. Objective: This study aimed to evaluate the effectiveness of regional nerve blocks versus standard opioid-based analgesia in reducing postoperative pain scores and opioid consumption, improving patient satisfaction, and minimizing adverse effects among breast cancer patients undergoing mastectomy. Methods: A descriptive cross-sectional study was conducted among female patients undergoing mastectomy or lumpectomy (n = 110) at two tertiary care hospitals in Lahore. Inclusion criteria were all ages, confirmed breast carcinoma, postoperative opioid or regional block analgesia, and informed consent; exclusion criteria included use of other analgesics or non-breast oncology procedures. Pain was assessed at 0, 6, 12, and 24 hours postoperatively using the Visual Analogue Scale (VAS) and opioid consumption was recorded. Data was analyzed using SPSS version 26, with t-tests, regression, and chi-square analyses as appropriate. The study received ethical approval in accordance with the Declaration of Helsinki. Results: Regional nerve block recipients had significantly lower opioid use at 0, 6, 12, and 24 hours (mean reduction: 7.2 mg; p < 0.001, Cohen’s d > 1.5), lower pain scores (VAS difference: 2.6 points; p < 0.001), and higher satisfaction (mean 9.0 vs 6.8 at 24 hours). The incidence of opioid-related side effects was reduced from 36% to 8% by 24 hours in the regional group. Conclusion: Regional nerve blocks significantly reduce pain scores, opioid consumption, and opioid-related side effects while improving patient satisfaction after breast cancer surgery. These findings advocate for wider adoption of regional anesthesia as a core component of postoperative pain management, advancing safer and more effective care for breast cancer patients.